Ni-catalyzed asymmetric hydrophosphinylation of conjugated enynes and mechanistic studies - Zhang, Ya-Qian; Han, Xue-Yu; Wu, Yue; Qi, Peng-Jia; Zhang, Qing; Zhang, Qing-Wei (Chemical science (Cambridge), 2022)
The catalytic asymmetric synthesis of P -stereogenic phosphines is an efficient strategy to access structurally diverse chiral phosphines that could serve as organocatalysts and ligands to transition metals and motifs of antiviral drugs. Herein, we describe a Ni catalyzed highly regio and enantioselective hydrophosphinylation reaction of secondary phosphine oxides and enynes. This method afforded a plethora of alkenyl phosphine oxides which could serve as valuable precursors to bidentate ligands. A new type of mechanism was discovered by combined kinetic studies and density functional theory (DFT) calculations, which was opposed to the widely accepted Chalk-Harrod type mechanism. Notably, the alkene moiety which could serve as a directing group by coordinating with the Ni catalyst in the transition state, plays a vital role in determining the reactivity, regio and enantioselectivity. A Ni-catalyzed hydrophosphinylation reaction of enynes was reported with excellent regio and enantioselectivity. A protonation mechanism was uncovered by combined kinetic studies and DFT calculations, which may lead to the discovery of other hydrofunctionalization reactions.